2011
DOI: 10.1002/pen.21920
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of contributing factors to production of highly transparent isotactic polypropylene extrusion sheets. Part 2

Abstract: To obtain highly transparent isotactic polypropylene (PP) sheet by an industrial process, the influences of the isotacticity and metallocene linear low‐density polyethylene (L‐LDPE) as crystallization control material were analyzed. The sheet samples were extruded by using a direct single‐belt process. Even if the sheeting was carried out under the same conditions, the lower tacticity PP generated the less and the smaller size of spherulites. Low‐tacticity PP showed improvement on transparency by heat treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…[91] Note that further data about the size of nodules in quenched iPP were collected by X-ray scattering techniques, [92][93][94][95][96][97] as well as that the correlation between the coolingrate dependent nucleation-controlled semicrystalline morphology and optical properties is also applied in industry, for example, for preparation of highly transparent films. [98,99] The above-described cooling-rate-controlled formation of largely different semicrystalline morphologies in polymers is a general phenomenon, as it is demonstrated with a further example in Figure 7. PA 11 films have been cooled at different rates, with the first derivative of the recorded cooling curves, that is, the cooling rate, plotted as a function of temperature in the graph to the left.…”
Section: Morphology Of Rapidly Cooled Filmsmentioning
confidence: 67%
See 1 more Smart Citation
“…[91] Note that further data about the size of nodules in quenched iPP were collected by X-ray scattering techniques, [92][93][94][95][96][97] as well as that the correlation between the coolingrate dependent nucleation-controlled semicrystalline morphology and optical properties is also applied in industry, for example, for preparation of highly transparent films. [98,99] The above-described cooling-rate-controlled formation of largely different semicrystalline morphologies in polymers is a general phenomenon, as it is demonstrated with a further example in Figure 7. PA 11 films have been cooled at different rates, with the first derivative of the recorded cooling curves, that is, the cooling rate, plotted as a function of temperature in the graph to the left.…”
Section: Morphology Of Rapidly Cooled Filmsmentioning
confidence: 67%
“…Here, the domain size is somewhat larger than in case of TEM analyses, around 15 nm, which later on has been addressed as being caused by the interaction between the sample and AFM tip; AFM images collected with super‐sharp tips yielded a smaller nodule size, similar as obtained by TEM . Note that further data about the size of nodules in quenched iPP were collected by X‐ray scattering techniques, as well as that the correlation between the cooling‐rate dependent nucleation‐controlled semicrystalline morphology and optical properties is also applied in industry, for example, for preparation of highly transparent films …”
Section: Morphology Of Rapidly Cooled Filmsmentioning
confidence: 87%
“…This apparently accelerated the crystallization kinetics, while the samples crystallized from the melt were of course melted before annealing. This processing effect on polymer crystallization kinetics has already been evidenced for isotactic polypropylene [31,32]. 130 C, one observes that the spherulites obtained from the melt were much larger than the ones obtained from the glass.…”
Section: Pla Crystallization Kineticsmentioning
confidence: 78%
“…It appears from the existing literature that several approaches could be adopted to optimize the optical property of iPP via controlling its crystallization behavior, mainly including increasing the fraction of amorphous phase by chemical synthesis, destroying spherulite texture by hot or cold stretching, and reducing the size of spherulites by inclusion of anucleating agents (a-NAs). [10][11][12][13] Among them, incorporation of a-NAs is the most effective methodology for endowing iPP with transparency. Some papers have reported that a large reduction of haze occurs in iPP lled with only 0.1-1.0 wt% a-NAs.…”
Section: Introductionmentioning
confidence: 99%